ANALYSIS OF THE DETERMINATION OF SOLVENCY, TAX AVOIDANCE AND COMPANY AGE ON THE COST OF DEBT IN MANUFACTURING COMPANIES IN THE FOOD AND SUB SECTOR BEVERAGE YEAR 2016-2021 WITH SIZE COMPANY AS A VARIABLE INTERVENING - Egy Permana; Rizki Fillhayati Rambe; Ahmad Sani (Cattleya Darmaya Fortuna, 2023)
This study aims to determine the effect of solvency on firm size. The effect of tax avoidance on firm size, the effect of firm age on firm size, the effect of solvency has a significant effect on debt costs, the effect of tax avoidance on debt costs, the effect of firm age on debt, the effect of company size on debt costs, the effect of solvency on debt costs through company size , the effect of tax avoidance on the cost of debt through company size and the effect of company age on debt costs through company size in Food and Beverages Companies Listed on the Indonesia Stock Exchange in 2016-2021. The sampling technique uses purposive sampling, which means selecting samples based on certain criteria. The population in this study were 30 companies and the sample in this study was 18 companies x 6 years of research = 108 data. The analysis technique used is Path Analysis. The results showed that solvency has a significant effect on firm size, tax avoidance has a significant effect on firm size, firm age has a significant effect on firm size, solvency has a significant effect on debt costs, tax avoidance has a significant effect on debt costs, firm age has a significant effect on debt costs, company size has a significant effect on the cost of debt, solvency has a significant effect on the cost of debt through company size, tax avoidance has a significant effect on the cost of debt through company size and company age has a significant effect on debt costs through company size In Food and Beverage Companies Listed on the Indonesia Stock Exchange Year 2016-2021.